Transcribing the Venda tshikona reedpipe dance - Tracey, Andrew; Gumboreshumba, Laina (International Library of African Music, 2013)
Starting with the end result, the above transcription is the conclusion I came to after sitting with Laina Gumboreshumba for many hours, watching the videos she made during her recent doctoral research on the tshikona reedpipe dance of the Venda of Limpopo Province in the extreme north of South Africa. The transcription shown in Figure 2 is a skeleton version of the full pipe sound that contains all the information needed to grasp the structure of the sound and teach it or play it. There are always seven different pipes. A full tshikona group has far more than the seven pipes (nanga) shown, because all seven pipe numbers are doubled in every octave present in a group, so there may be up to four or more Pipe 1s, Pipe 2s, etc, of different sizes. All the Pipe 1s play the same pattern together, all the Pipe 2s etc. There are usually four octaves in all, with an incomplete octave of a few higher pitched pipes at the top (phalana). A popular size for a group according to group leaders (malogwane) is twenty eight pipes, which may include some pitch duplicates. A festive performance can number well over one hundred players. The music is heptatonic as you can see from the transcription, and hear for yourself from CD track 1 accompanying this issue of African Music. A chart showing the tuning is included as Figure 1 1 at the end of this article. This article does not address the pipe names; they are simply numbered Pipes 1 to 7, in the order of entry in Mr Netshivhale's groups. The pipes are end-blown, closed tubes made of a special bamboo, or increasingly today of electrical or other tubing.3 (See Figure 3)
Keywords: African Music